Journalistic Convergence in Digital Media Transformation: A Study on Sriwijaya Post and sripoku.com - Rustam; Isnawijayani; Misnawati, Desy; Amin, Zaid (Indonesian Scientific Publication, 2025)
This study examines the transformation of journalistic practices in response to digital media developments, focusing on Sriwijaya Post and Sripoku.com. Using a qualitative descriptive approach, data were collected through interviews and observations with journalists at both the field and editorial levels. The findings reveal that media convergence has significantly impacted journalistic workflows, necessitating journalists to adopt multimedia skills, including video production, real-time reporting, and social media engagement. This transformation involves structural and strategic newsroom changes to facilitate cross-platform content production. As part of a regional media network, Sriwijaya Post and Sripoku.com have embraced digital platforms for content delivery and as a primary revenue stream, particularly through services such as Google AdSense. The study contributes to a deeper understanding of how regional media in Indonesia navigate the challenges of digital convergence while maintaining journalistic integrity and sustaining their role in a rapidly evolving media ecosystem.